Foliar microbiota confers deeper color of fermented cigar wrapper under additional fermented bacteria - Qian Wu; Xuanshuang Duan; Dapeng Tang; Rui Wang; Fuqiang Li; Jun Tan; Honghua Chen; Shixue Zheng (Bioresources and Bioprocessing)
Abstract Microorganisms play an indispensable role in the fermentation of cigar tobacco such as improvement of flavor, aroma and quality. However, little is known about additional microorganism impact on shift of the color of cigar wrappers. Here, three bacterial strains that could alter the wrapper’s color were isolated and screened from cigar tobacco leaves (CTLs) at different stages of fermentation. The three strains were identified to be Sphingomonas parapaucimobilis DS1, Kosakonia cowanii DS101, and Comamonas thiooxydans DS309 based on the genome sequences. The overall color difference (∆E) of CTLs was significantly deepened with the addition of those three strains under upscaled stack fermentation, respectively (p ≤ 0.05), showing the same fundamental quality of cigar wrapper. The ascorbic acid oxidase activity was significantly decreased and cigarillo polyphenol oxidase activity was significantly increased added with the three bacteria compared to the control (p ≤ 0.05). Moreover, the exogenous strains substantially altered the community structure of the cigar wrapper. In particular, the abundance of dominant Staphylococcus nepalensis significantly increased under addition of strain DS101 and DS309 except for strain DS1 as dominant species. In addition, non-targeted metabolomics analyses showed that the exogenous microbial addition treatments demonstrated substantial variations in a variety of metabolites, including a reduced expression in the pathways related to the manufacture of polyphenols and unsaturated fatty acids (p ≤ 0.05). In conclusion, addition of bacteria DS1, DS101, and DS309 enhanced oxidation of polyphenols to brown quinones and oxidation of unsaturated fatty acids, resulting in membrane lipid peroxidation and then deepened the color of cigar wrappers. It provides a novel strategy to improve the color of cigar wrappers by utilizing additional bacteria in cigar fermentation.